Understanding farmers’ ecological conservation behavior regarding the use of integrated pest management- an application of the technology acceptance model - Rohollah Rezaei; Leila Safa; Mohammad Mahdi Ganjkhanloo (Global Ecology and Conservation, 2020)
Integrated Pest Management (IPM) is considered as an ecological conservation technology for crop pests’ management; however, the technology adoption is intensely affected by surrounding socio-psychological environment, which is poorly studied, particularly in developing nations. The present study therefore aimed at addressing this gap through application of an extended form of Technology Acceptance Model (TAM) in order to examine the determinants of Iranian farmers’ ecological conservation behavior regarding the use of IPM practices. This research was a descriptive, causal, and correlational study conducted through a cross-sectional survey of 327 tomato growers in Zanjan Province of Iran. The results disclosed that the growers utilize various IPM practices (cultural, mechanical, chemical, and biological); nevertheless, the majority of growers were grouped in relatively low or low level of IPM practices’ usage. The key propositions of the original TAM, i.e., attitude, perceived usefulness, and perceived ease of use, explained 41.3% of the variance in the farmers’ ecological conservation behavior regarding IPM practices’ application. Moreover, the extended TAM was appropriate for the prediction of effective factors of farmers’ ecological conservation behavior concerning the use of IPM practices. Also, adding the four constructs of social influence, result demonstrability, compatibility, and self-efficacy, significantly enhanced the stability and explanatory power of the original TAM (from 41.3% to 46.4%). In the extended TAM, result demonstrability (β = 0.182) and compatibility (β = 0.360) had significant positive impacts on perceived usefulness; while, self-efficacy had a meaningful positive effect on perceived ease of use (β = 0.776), and had not any impact on perceived usefulness (β = 0.114). The findings of this study expanded the current body of knowledge on technology acceptance via the investigation of TAM in a novel ecological conservation technology field (i.e., the IPM technology) and provided a roadmap for better understanding of decisive factors affecting farmers’ ecological conservation behavior as well as post-implementation interventions aiming at IPM technology promotion in developing countries.